FUTURE OF ONLINE LEARNING AND ITS EFFECT ON THE JOB MARKET- AN EMPIRICAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
In the past, job or placement outcomes have been at the centre of educational research. But the empirical research that has been done so far only looks at face-to-face education. There is no scientific study that looks at how online learning affects the job market. This study looks at the online learners in India. It uses data from a survey of private universities and colleges in Tamil Nadu, India, to show how online education and job match are linked. The goal of this study is to fill a gap in the research field by looking at how people in India learn online. Because of the empirical research, two important things were found. First of all, there is no difference in the job market between people who learn in person and people who learn online. The human capital theory is used in this study to try to explain why this is happening. According to this theory, there is no difference between offline learners and online learners in terms of how they get their human capital. As a result, both types of learners prefer to work in jobs that are a good fit for them. Second, employment mismatch doesn't have a big effect on the income of people who learn their skills online. The screening theory is used in this study to try to explain why this is happening. Even though this theory says that online education would improve the human capital of each learner, it still acts as a diploma/ degree signal in India, at least in some ways. Because of this, the human capital that online learners gain can't be turned into a higher income. Because of this, it is important to look into the link between online education and employment. This study will look at how online learning affects career opportunities and how work match affects how much money online learners make. This study will also look at how job match affects the income of people who learn online. This study looks into the job market for online learners. The results could help academics and policymakers better understand what online education is for and how important it is as a study method for tertiary education.